Does Transparency Lead to Pay Compression? - Mas, Alexandre (The Journal of political economy)
This paper asks whether pay disclosure in the public sector changes wage setting at the top of the distribution. I examine a 2010 California mandate that required municipal salaries to be posted online. Among top managers, disclosure led to approximately 7 percent average compensation declines, and a 75 percent increase in their quit rate, relative to managers in cities that had already disclosed salaries. The wage cuts were largely nominal. Wage cuts were larger in cities with higher initial compensation, but not in cities where compensation was initially out of line with (measured) fundamentals. The response is more consistent with public aversion to high compensation than the effects of increased accountability.